The Phenomenon of Phubbing in Interpersonal Communication Among Teenagers in Cirebon - Fauziah, Riska; Khumayah, Siti; Wihayati, Welly (International Journal of Social Service and Research, 2026)
Phubbing is the act of someone ignoring the people around them because they are too focused in using their cell phones. Among adolescents, phubbing has now become a serious issue in social interactions. This study has the aim to find out about the various forms of phubbing, the triggering factors, the impact on victims, as well as the effectiveness of interpersonal communication regarding phubbing among adolescents in Cirebon. A descriptive qualitative method and purposive sampling were implemented for this study, involving six informants, which comprises three perpetrators and three victims of phubbing. Through in-depth interviews as well as observation, data were collected and then analyzed with the Miles and Huberman model. The findings revealed that there are five forms of phubbing behavior and there are five main factors that trigger it, which are dependency on social media, poor skills of communication, low self-control, Fear of Missing Out (FoMO), along with the influence of social environment. The findings indicate that phubbing leads to ineffective interpersonal communication, as evidenced by disruptions in the five elements of communication: openness, empathy, positive attitude, support, and equality. This study emphasizes the importance of digital literacy in raising adolescents’ awareness of the value of full presence in social interactions.